THE ART OF FLYING IN O VIDIUS : THE EFFECT OF PREVERBS ON MANNER OF MOVEMENT VERBS - Nieto Manini, Ana Lorena (AADEC - UNL, 2018)
From a functional and cognitive linguistic paradigm, the effect of preverbs added is studied in a Manner of Motion Verb: volare. The corpus is established from all Ovid’s poetic work from the study of semantic and grammatical difference of volare in simple or compound form, and the alteration of the telicity and transitivation of the clauses. Latin is a satellite-framed language and therefore the addition of preverbs will corroborate or not the hypotheses established about their effects.